Ekstrak Etanol Daun Kelor (Moringa oleifera Lam.) Sebagai Antioksidan Dalam Pengencer Semen Babi Landrace Berbasis Air Buah Lontar - Maria Gisela Goncalves Gena; Nancy D F K Foeh; Cynthia Dewi Gaina (Jurnal Veteriner Nusantara, 2021)
This study aims to determine the antioxidant effect of the ethanol extract of the leaves of Moringa (Moringa oleifera Lam.) In water diluent palm fruit of the quality of landrace pig spermatozoa. This study uses a Completely Randomized Design (CRD) with 5 treatments, 1 control dan 4 repetitions and observation of the motility and viability of spermatozoa performed every 2 hours until a decline in the percentage motility of at least 40%. The cement used in the Laboratory of Technical Services Unit for Breeding and Forage at Tarus, Kupang. Escrow done every two weeks from the male landrace pigs who have experienced sexual maturity. Landrace pig semen storage results were evaluated macroscopically and microscopically. Good quality cement had ≥70% motility, concentration ≥200x106 sel spermatozoa/ml and abnormalities of ≤20%. Cement is added to the water diluent palm fruit then added with antioxidants. Antioxidants should be added during the storage process, sperm metabolic activity produces free radicals that can degrade the quality of spermatozoa. Moringa leaves (Moringa oleifera Lam.) Is one of the antioxidants that can be used to counteract free radicals. Moringa leaves (Moringa oleifera Lam.) Is added to the water diluent palm fruit with graded doses are 1% (P1), 2% (P2), 3% (P3), 4% (P4) and 5% (P5). The results of this study indicate a dose of 1% (P1) is the best dosage to maintain the quality of the landrace pig spermatozoa of 66.25 ± 2.39 motility and viability of spermatozoa sebesar 78.00% ± 1.82%, which is stored at room temperature 22º C.